Interactive Modeling of Green Supply Chain Management Components in Sports Businesses: A Process-Oriented and Hierarchical Approach - Zahra Sadeqi-Arani; Ebrahim Alidoust Ghahfarokhi; Mahdi Omidvar Ashklak (Shahid Bahonar University of Kerman, 2022)
This article aims to identify the relationships among components of green supply chain management (GSCM) in sport businesses through interpretive structural modeling (ISM) and classifying those components according to their driving and dependence power. This study developed in two phases. In the first phase, literature was reviewed and 12-components of GSCM were identified. Then, in the second phase, the GSCM components in sports businesses were structured using ISM and the hierarchical and interactive model of GSCM in sports businesses was developed. The results showed that among the 12-components, 'internal/external pressure', 'rules, regulations and standards' and 'green resources' were the drivers and cornerstones of the formation and change of other factors. Based on the research findings, the key driver and components for achieving GSCM in sports businesses are providing infrastructure (green resources), adhering to norms (internal and external pressure), and setting its executive guarantees (rules, regulations and standards). Therefore, to achieve 'economic benefits' and create a 'green market' in the sports industry, emphasis and investment on these issues will be helpful. The current paper attempts to develop a conceptual framework for GSCM in sports businesses.